Determining PM10 Model in Hanoi Using Landsat 8 Oli and Ground-measured Dust Data - Hung, Nguyen Nhu; Anh, Tran Van; Vinh, Pham Quang; Binh, Nguyen Thanh; Hoang, Vu Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1DO - 10.25073/2588-1094/vnuees.4146, 2018)
PM10 (Particulate matter 10 is a dust with aerodynamic diameters of 0.001 ÷ 10μm) is one of the air pollutants affecting human health. In this study, we conducted a modeling study to identify PM10 dust in the air by using Landsat 8 OLI satellite image, along with PM10 ground-measured data using the machine DustTrak II . Conduct regression analysis to determine the correlation model. Here, we used 16 in-situ measurement points. In that, 10 points were used to determine the regression function and 6 other points were used to test the regression model. Results were evaluated based on correlation coefficient (R) and Root Mean Square Error (RMSE) between measured and calculated data.